The digital transformation of healthcare - An interview with Werner Dorfmeister - Rainer Alt; Hans-Dieter Zimmermann (Electronic Markets, 2021)
In this interview, Werner Dorfmeister, a Vice President at DasLab and a former Global Sales Director at Karl Storz, reports on the current~developments of digital technologies in the field of medical instruments and services. It is a sector where digitalization affects all processes within hospitals as well as pre- and post-surgical activities. Due to the many actors involved, who use different information systems, and the strong regulation of the entire~healthcare sector, crafting digital solutions is complex, but nevertheless promising and necessary. Among the key areas mentioned in the interview are telemedicine, hospital and patient~management and a sector-wide digital infrastructure. Digital platforms are described as important enablers to address current inefficiencies and to leverage~future potentials towards patient-orientation, such as digital patient pathways.
Keywords: 620; Digital transformation; Healthcare industry; Digital patient pathways